2001
DOI: 10.1073/pnas.041493198
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 inhibits osteoclast formation through a direct action on osteoclast precursors via peroxisome proliferator-activated receptor γ1

Abstract: IL-4 is a pleiotropic immune cytokine secreted by activated TH2 cells that inhibits bone resorption both in vitro and in vivo. The cellular targets of IL-4 action as well as its intracellular mechanism of action remain to be determined. We show here that IL-4 inhibits receptor activator of NF-B ligand-induced osteoclast differentiation through an action on osteoclast precursors that is independent of stromal cells. Interestingly, this inhibitory effect can be mimicked by both natural as well as synthetic perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 37 publications
5
103
0
1
Order By: Relevance
“…6A). The second strategy used the specific PPAR␥ inhibitor GW9662 (27). Consistent with the studies using the PPAR␥ dominant-negative mutant, pretreatment with the PPAR␥ antagonist GW9662 blocked the ability of ciglitazone, as well as cellular homogenates from UVB-irradiated cells or UVB-irradiated HAPC, to augment PMA-induced COX-2 expression in KB cells (Fig.…”
Section: Methodsmentioning
confidence: 74%
“…6A). The second strategy used the specific PPAR␥ inhibitor GW9662 (27). Consistent with the studies using the PPAR␥ dominant-negative mutant, pretreatment with the PPAR␥ antagonist GW9662 blocked the ability of ciglitazone, as well as cellular homogenates from UVB-irradiated cells or UVB-irradiated HAPC, to augment PMA-induced COX-2 expression in KB cells (Fig.…”
Section: Methodsmentioning
confidence: 74%
“…Several mechanisms have been proposed for these effects: antagonism of the RANKL-activated NF-B and mitogen-activate protein kinase pathways (30,31,34,43), down-regulation of NFATc1 and c-Fos expression in progenitor cells (32), regulation of Ca 2ϩ signaling (31), regulation of PPAR␥1 (33), and suppression of RANK expression (29). We previously reported that the inhibitory effects of IL-4 on the bone resorbing activity of osteoclasts are STAT6-dependent (29).…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting, as IL-4 is one of the most potent suppressors of osteoclast formation [25]. IL-4 inhibits osteoclast differentiation through directly activating PPARg [26], which is a potent transcriptional suppressor for osteoclast differentiation [27]. Moreover, IL-4 neutralizes the action of RANKL on osteoclasts by suppressing activation of NF-kB [14] and also effectively blocks TNF-a-mediated osteoclast formation [28].…”
mentioning
confidence: 99%